A perícia psicológica envolvendo suspeitos de abuso sexual contra crianças e adolescentes - Silva, Alessandra Manéa da (Universidade do Vale do Rio dos Sinos, 2020)
Evidences of sexual abuse isn’t always physical, or easy to collect from children and adolescents. For this reason, police and judicial authorities have requested the help of psychologists to investigate and produce technical evidences. The participation of the alleged aggressors in psychological investigations is not a consensus among professionals in the field, who often restrict their assessments to the child and one of their guardians. The present study aimed to find out how psychological investigations involving suspected of sexual abuse against children and adolescents are carried out. To this end, a qualitative research was carried out, with four professional psychologists working in the area, in order to investigate their ways of preparing psychological assessments as well as what are the challenges encountered, procedures and instruments used, the difficulties and especially the perception of inclusion of alleged aggressors in the forensics. The results indicated that there is no standard for preparing the assessment, but the professionals emphasize the importance of the suspect's participation in the procedures. They feel prepared for this type of work, but they understand the complexity and emphasize the importance of technical qualification and the development of specific instruments. Still, they inform that they try to be objective and clear in their documents, with regard to presenting the results of the evaluation. This study demonstrates the need to rethink the benefits of including the alleged abuser in psychological expertise, as well as the importance of developing tools that can assist in this process.
Keywords: Abuso sexual; Suposto agressor; Perícia psicológica; Sexual abuse; Supposed aggressor; Forensic psychological evaluation